Mirada a la cultura wayúu, base de su sistema normativo (2014)
the wayuu ethnic group, one of our native cultures that doesn’t want disappear, is located in the Guajira Peninsula in northern Colombia. Four are the pillars of this culture: The legal system, or common law; the pütchipü’üi or “palabrero” as the guardian of this system; the ouutsü women, its spiritual pillar, and the wayuunaiki, its mother tongue. These pillars are the object of this communication. This article, a preliminary report on an investigation into the culture that gives rise to that legal system, intendeds to visualize some aspects of that culture in order to assist in its protection as mandated by the Constitution of Colombia.